Transient Elastography for Significant Liver Fibrosis and Cirrhosis in Chronic Hepatitis B: A Meta-Analysis - Xiaolong Qi; Min An; Tongwei Wu; Deke Jiang; Mengyun Peng; Weidong Wang; Jing Wang; Chunqing Zhang; on behalf of the CHESS Study Group (Canadian Journal of Gastroenterology and Hepatology)
Background. The hepatitis B virus infection is a global health issue and the stage of liver fibrosis affects the prognosis in patients with chronic hepatitis B (CHB). We performed the meta-analysis describing diagnostic accuracy of transient elastography (TE) for predicting CHB-related fibrosis. Methods. We performed an adequate literature search to identify studies that assessed the diagnostic accuracy of TE in CHB patients using biopsy as reference standard. Hierarchical summary receiver-operating curves model and the bivariate mixed-effects binary regression model were applied to generate summary receiver-operating characteristic curves and pooled estimates of sensitivity and specificity. Results. The area under the summary receiver-operating curve for significant fibrosis and cirrhosis was 0.86 (95% confidence interval (CI): 0.83–0.89) and 0.92 (95% CI: 0.90–0.94), respectively. The sensitivity, specificity, and diagnostic odds ratio of TE for significant fibrosis were 0.78 (95% CI: 0.73–0.81, p<0.01; I2=85.59%), 0.81 (95% CI: 0.77–0.84, p<0.01; I2=88.20%), and 14.44 (95% CI: 10.80–19.31, p<0.01; I2=100%) and for cirrhosis were 0.84 (95% CI: 0.80–0.88, p<0.01; I2=76.67%), 0.87 (95% CI: 0.84–0.90, p<0.01; I2=90.89%), and 36.63 (95% CI: 25.38–52.87, p<0.01; I2=100%), respectively. The optimal cut-off values of TE were 7.25 kPa for diagnosing significant fibrosis and 12.4 kPa for diagnosing cirrhosis, respectively. Conclusion. TE is of great value in the detection of patients with CHB-related cirrhosis but has a suboptimal accuracy in the detection of significant fibrosis.